2001
DOI: 10.1097/00004714-200108000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized Comparison of the Efficacy and Safety of Intramuscular Injections of Olanzapine, Lorazepam, or Placebo in Treating Acutely Agitated Patients Diagnosed With Bipolar Mania

Abstract: There are no rapid-acting intramuscular formulations of atypical antipsychotics available for quickly calming an agitated patient with bipolar disorder. In this study, 201 agitated patients with bipolar mania were randomly assigned to receive one to three injections of the atypical antipsychotic olanzapine (10 mg, first two injections; 5 mg, third injection), the benzodiazepine lorazepam (2 mg, first two injections; 1 mg, third injection), or placebo (placebo, first two injections; olanzapine, 10 mg, third inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
4
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(151 citation statements)
references
References 20 publications
9
133
4
3
Order By: Relevance
“…It is of clinical importance that the improvement, as measured by the drop in the Young Mania Rating Scale (YMRS) scores, did not differ between psychotic and nonpsychotic manic patients. In addition, a randomized, controlled trial of injectable olanzapine in agitated mania has demonstrated significant superiority for olanzapine against placebo and lorazepam after 2 h (Meehan et al 2001).…”
Section: Olanzapinementioning
confidence: 99%
“…It is of clinical importance that the improvement, as measured by the drop in the Young Mania Rating Scale (YMRS) scores, did not differ between psychotic and nonpsychotic manic patients. In addition, a randomized, controlled trial of injectable olanzapine in agitated mania has demonstrated significant superiority for olanzapine against placebo and lorazepam after 2 h (Meehan et al 2001).…”
Section: Olanzapinementioning
confidence: 99%
“…Because of the strength of evidence for efficacy in alleviating agitation in this population, aripiprazole IM (level 2),125, 126 lorazepam IM (level 2),125, 127 loxapine inhaled (Level 1)128, 129 and olanzapine IM (level 2)127, 130, 131, 132, 133 are recommended as the first‐line option. Sublingual asenapine (level 3),134 haloperidol IM (level 3),131, 135, 136 haloperidol IM + midazolam IM (level 3),131, 137 haloperidol IM + promethazine IM (level 3),131, 137, 138 risperidone ODT (level 3),136 and ziprasidone IM (level 3)131, 137, 139 are recommended as a second‐line treatment.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…In a trial involving patients with schizophrenia, the NNT for 10 mg olanzapine was 3 (95% CI 2-3). In bipolar I mania, 10 mg olanzapine also yielded an NNT of 3 (95% CI 2-5) (Meehan 2001). Intramuscular olanzapine is as efficacious as haloperidol and has significant advantages in terms of extrapyramidal symptoms: Parkinsonism was avoided in 1 in 7 patients, acute dystonia in 1 in 14, and anticholinergic prescrip tions were avoided in 1 in 7 patients (Tulloch 2004;Citrome 2007).…”
Section: Olanzapinementioning
confidence: 99%
“…The consensus guidelines mentioned above (Expert Consensus Panel for Behavioral Emergencies 2005) currently recommend atypical antipsychotics as first-line agents for acute agitation in schizophrenia, although evidence of atypical antipsychotic efficacy in managing agitation in bipolar I disorder has also been established (Meehan 2001;. Olanzapine and risperidone are both available in disintegrating oral tablets and are therefore optimal as first-line interventions for patients who will take them.…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%